ANALISIS KEBUTUHAN TOPIK PEMBELAJARAN LITERASI INFORMASI ONLINE PADA PERPUSTAKAAN SEKOLAH MAN INSAN CENDEKIA - Deliasari, Arieni; Kurnianingsih, Indah (Edulib, 2017)
In each design activities, required analysis of user needs for the results obtained to meet the objectives to be achieved. This research is descriptive qualitative research which aims to get an analysis of learning needs LI material online that required student MAN Insan Cendekia Serpong. Thenumber of samples in this study was 54 students. The data taken is analized based on the indicators of LI which refers to Information Literacy Competency Standard for Higher Education which is released bythe Association of College Research Libraries (ACRL), combined with School Library Manifest which is published by International Federation of Library Association of College Research Libraries (IFLA/UNESCO). The results of the research indicated that respondents have good ability in terms of 1) determining the limits of information, accessing information needed effectively and efficiently, 2) combining selected information into one's knowledge base, 3) ability to understand economic issues,law, and social use of information and access it ethically and legally. The abilities which are needed to increase is in evaluating information and the sources, and ability to use information effectively to achieve the particular goals. Six tops materials which are selected by students in designing information literation based on web, are 1) orientation in library including collection items and loations, 2) the technique of index using, reference materials and bibliography, 3) Techinques in searching information, 4) Technique of Online catalogue use, 5) Ways to use reference sources which is matched the needs, 6) Technique of reference writing.